2021
DOI: 10.1182/hematology.2021000271
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of somatic transformation in inherited bone marrow failure syndromes

Abstract: Inherited bone marrow failure syndromes (IBMFS) cause hematopoietic stem progenitor cell (HSPC) failure due to germline mutations. Germline mutations influence the number and fitness of HSPC by various mechanisms, for example, abnormal ribosome biogenesis in Shwachman-Diamond syndrome and Diamond-Blackfan anemia, unresolved DNA cross-links in Fanconi anemia, neutrophil maturation arrest in severe congenital neutropenia, and telomere shortening in short telomere syndrome. To compensate for HSPC attrition, HSPCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 50 publications
(57 reference statements)
1
12
0
Order By: Relevance
“…Due to the rapid renewal of bone marrow hematopoietic cells, ribosome biogenesis is involved in this process. 261 , 262 Therefore, the blood system is more vulnerable to ribosome dysfunction. It has been shown that some blood diseases are associated with ribosome dysfunction.…”
Section: Ribosome and Blood Diseasesmentioning
confidence: 99%
“…Due to the rapid renewal of bone marrow hematopoietic cells, ribosome biogenesis is involved in this process. 261 , 262 Therefore, the blood system is more vulnerable to ribosome dysfunction. It has been shown that some blood diseases are associated with ribosome dysfunction.…”
Section: Ribosome and Blood Diseasesmentioning
confidence: 99%
“…The mutational spectrum in IBMFS is different from that in the general elderly population, as epigenetic regulators, such as DNMT3A, TET2, and ASXL1 , the most frequently mutated genes in the elderly population, are relatively rare. Instead, somatic genomic alterations that can restore the original function of a protein or allow pathological adaptation for survival are preferentially selected for clonal expansion [ 34 ]. Based on current knowledge, unless accompanied by high-risk cytogenetic abnormalities, progressive cytopenia and/or BM morphologic changes, clonal hematopoiesis itself does not require immediate definitive treatment even in the setting of IBMFS [ 34 ].…”
Section: Clonal Hematopoiesis In Inherited Bone Marrow Failure Syndromementioning
confidence: 99%
“…Instead, somatic genomic alterations that can restore the original function of a protein or allow pathological adaptation for survival are preferentially selected for clonal expansion [ 34 ]. Based on current knowledge, unless accompanied by high-risk cytogenetic abnormalities, progressive cytopenia and/or BM morphologic changes, clonal hematopoiesis itself does not require immediate definitive treatment even in the setting of IBMFS [ 34 ].…”
Section: Clonal Hematopoiesis In Inherited Bone Marrow Failure Syndromementioning
confidence: 99%
“…Patients with FA have a 30% to 40% cumu la tive risk of mye loid malig nan cies by age 40 years. 17,18 These often arise from clonal kar yo type abnor mal i ties and unbal anced trans lo ca tions, lead ing to gains or losses of chro mo somes. Some cyto ge netic changes pre dict neg a tive out comes, and their iden ti fi ca tion is impor tant to decide the tim ing of HSCT 19,20 (Figure 1).…”
Section: Clonal Evo Lu Tionmentioning
confidence: 99%
“…ily indi cate impending trans for ma tion. 18 Conversely, mono somy 7/del(7q) is con sid ered a marker of trans for ma tion, requir ing urgent HSCT. 18 Other cyto ge netic changes indi cat ing a poor prog no sis are gain of chro mo some 3q, fre quently pre ced ing mono somy 7/del(7q), 21,22 and RUNX1 abnor mal i ties, includ ing cryp tic trans lo ca tions, that also indi cate imme di ate HSCT.…”
Section: Search Of Hla-matched Unre Lated Donor If No Healthy Hla-mat...mentioning
confidence: 99%